PLANT SPECIATION THROUGH CHROMOSOME INSTABILITY AND PLOIDY CHANGE: CELLULAR MECHANISMS, MOLECULAR FACTORS, AND EVOLU-TIONARY RELEVANCE - P. PANDE PIER, M.A. FACET, M. BREGER, P. BREGER (International Journal of Multidisciplinary Research and Studies, 2021)
Plant speciation and diversification strongly depend on structural changes within the nuclear genome, both at the entire ploidy and individual chromosome level. Phylogenetic, comparative mapping, and cytological studies have provided insights into the evolutionary mechanisms that shape the plant genome. These include major genome alterations, like whole-genome duplication and hybridization (auto- and allopolyploidy), but also comprise the concomitant or independent occurrence of minor chromosome changes, like aneuploidization and dysploidy (inversions and translocations). Despite the relevance of chromosomal instability as a driver for genome evolution and adaptation, little is yet known about the cellular mechanisms and processes that really underlie these modifications. Here, during this paper, we offer a comprehensive overview of somatic and meiotic defects that cause polyploidy or structural genome changes and discuss their relevance for plant genome evolution and speciation. Also, we elaborate on the existence of stress-induced changes in chromosome and ploidy integrity in plants and their putative role in boosting adaptive genome evolution in hostile environments.